1792 illustration of the Treaty of Sistova - Daniel Nikolaus... (Wikimedia Commons)
Notice iconographique issue de Wikimedia Commons. Titre: 1792 illustration of the Treaty of Sistova. 1792 illustration of the Treaty of Sistova
Licence Public domain via Wikimedia Commons
Keywords: iconographie; illustration; gravure; patrimoine; wikimedia commons